2015
DOI: 10.1021/acs.jpcb.5b01219
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Multifilament Structures and Lateral Interactions in Dynamics of Cytoskeleton Proteins and Assemblies

Abstract: Microtubules and actin filaments are biopolymer molecules that are major components of cytoskeleton networks in biological cells. They play important roles in supporting fundamental cellular processes such as cell division, signaling, locomotion, and intracellular transport. In cells, cytoskeleton proteins function under nonequilibrium conditions that are powered by hydrolysis of adenosine triphosphate (ATP) or guanosine triphosphate (GTP) molecules attached to them. Although these biopolymers are critically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…As long as this constraint is satisfied, the update rules can be chosen following local detailed balance R + /R − = e −βǫ , where R + is the rate of a process that has a positive energy cost ǫ and R − is the rate of the reverse process. The filaments are modeled as rigid rod-like polymers, composed of monomers of length d [27,[36][37][38]. In Fig.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…As long as this constraint is satisfied, the update rules can be chosen following local detailed balance R + /R − = e −βǫ , where R + is the rate of a process that has a positive energy cost ǫ and R − is the rate of the reverse process. The filaments are modeled as rigid rod-like polymers, composed of monomers of length d [27,[36][37][38]. In Fig.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…In this paper we have provided a theoretical framework to understand and predict the cooperative effects in the maximum force generation by multiple motors or filaments, for a broad class of models. It is now appreciated, at least theoretically, that the stall force of individual cytoskeletal filaments or molecular motors, when they push together against some obstacle, is not additive in general [31,32,57]. In this paper, we have provided several pointers to show that this non-additivity of the stall forces (f (N )…”
Section: Discussionmentioning
confidence: 93%
“…Some of these theoretical studies have demonstrated that the stall force of multiple, non-interacting filaments without ATP/GTP dynamics, scales linearly with the number of filaments [26,[28][29][30]54]. In contrast, a few other recent papers quite clearly report that inclusion of ATP/GTP hydrolysis can lead to either enhanced or reduced cooperativity in the maximum force generated by multiple growing filaments; the stall forces need not always scale with the number of filaments [31,[56][57][58]. In other words, the stall forces of individual filaments are non-additive in general, that is, the collective stall force produced by N number of filaments (denoted by f (N ) s ) is not just a simple sum of individual stall forces of single filaments (i.e., f (N )…”
Section: Introductionmentioning
confidence: 99%
“…Most of the mathematical models that dealt with polymerization-driven force generation do not explicitly consider the wall movements. Rather, the presence of wall is encapsulated in the growth rate and detachment rate of the filament [16,17,[19][20][21]. In these 'Brownian ratchet' models, the filament in contact with the wall is assumed to grow with an on-rate proportional to exp (−qf δ/k B T ) and off-rate proportional to exp (−(q − 1)f δ/k B T ) with 'q' being the load sharing factor.…”
Section: Mathematical Formalism: Fokker-planck Equationsmentioning
confidence: 99%